"My children do not deserve it": Understanding how epiphanies instigate support-seeking practices among veteran families living with PTSD in Denmark - Jeanette Bonde Pollmann; Morten Skovdal (Elsevier, 2022)
Post-deployment posttraumatic stress disorder (PTSD) does not merely affect veterans. A growing body of literature highlights the detrimental impact of veteran PTSD on entire families. One area less studied pertains to how PTSD affects veterans' parenting skills and engagement with social support structures in response to family struggles. Through an interpretative phenomenological analysis, we addressed this gap by drawing on qualitative research with six Danish veteran families affected by PTSD. We applied a theoretical lens of epiphanies as turning points to explore the interface between experiences of the impact of PTSD on the family system and support-seeking practices within the families' social networks. Aided by Denzin's notion of epiphany, we locate and report on the occurrence of four types of epiphanies that instigate help-seeking. The epiphanies reveal details about parents' experiences of the effect of PTSD on family life, as well as their needs and responses to struggles of parenting and children's distress. The epiphanies also serve as critical enablers of PTSD-affected veterans and their families' engagement in support-seeking practices. Social support services aiming to help veteran families should consider how parenting experiences and epiphanies can mobilize pathways to social support.